Czy korporacje mogą praktykować religię? Sprawa Burwell v. Hobby Lobby Stores, Inc. - Bury, Paweł (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The article is focused on the differences and similarities between the legal system in the United States of America and the legal system in Poland. The background to these considerations is the United States Supreme Court judgment in Burwell v. Hobby Lobby case. The Court held at the time that closely held for-profit corporations may be exempt from a generally applicable law if their owners have religious objections. This article describes also the free exercise of religion and kinds of free-exercise claims in the applicable legal regulation in Poland.
Keywords: Patient Protection and Affordable Care Act; for-profit corporations; conscience clause; First Amendment to the United States Constitution; conscientious objection; Free Exercise Clause; Religious Freedom Restoration Act